Preparation of nanostructured energetic materials by sol-gel technology - Holub, Petr; Vávra, Pavel (Univerzita Pardubice, 2006)
The conditions have been experimentally specified for formation of a xerogel of nano-structured energetic materials by the sol-gel method. Using an example of the system of resorcinol-formaldehyde and ammonium perchlorate, the limiting factors for the formation of nano-particles were found to include: the water content in the primary sol, the solubility of ammonium perchlorate, and the rate of drying of the gel formed. It has been found that increased temperature results in distinct shortening of the time of formation of the gel.
Keywords: nanostruktura; energetické materiály; koloidní systémy; metody přípravy